HUBUNGAN KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL DENGAN KENAKALAN REMAJA DI SMK SORE PANGKALPINANG TAHUN 2023 - Prasetya, Raynaldi (Coping: Community of Publishing in Nursing; Vol 11 No 6 (2023): Desember 2023, 2024)
Juvenile delinquency is behavior that is not in accordance with social norms, laws, religions, and applicable community rules. Juvenile delinquency can have a negative impact on adolescents. Now this behavior tends to develop into criminal acts that violate the law. One of the factors that influence juvenile delinquency is emotional and spiritual intelligence because both are interrelated and influence each other's behavior. The purpose of this study was to determine the relationship between emotional intelligence and spiritual intelligence with juvenile delinquency at SMK Sore Pangkalpinang in 2023. This research design is a quantitative study using the cross sectional method. The sample in this study were X and XI grade students of SMK Sore Pangkalpinang in 2023, totaling 86 students. Data collection instruments in this study were questionnaires and data analysis from this study was analyzed using the Pearson test. The results of this study indicate that there is a relationship between emotional intelligence and juvenile delinquency (p = 0,002 < 0,05) and there is a relationship between spiritual intelligence and juvenile delinquency (p = 0,001 < 0,05).